2019
DOI: 10.20429/ijsotl.2019.130307
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Course Syllabi: The Role of Syllabi in Motivating Students

Abstract: In this mixed methods study, researchers explored students' perceptions of different types of syllabi, the course, and the instructor articulated through the syllabi. Students were randomly assigned to read one of two US History syllabi: a content-focused syllabus (CFS), characterized as a traditional, content-focused, policy-laden syllabus; or a learning-focused syllabus (LFS), characterized by strong learning objectives, authentic assessments, and a positive, motivating tone. Results show that LFS participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…9 A learning-focused syllabus can communicate to students that the course is interesting and rigorous and that the instructor cares about and is important to their success. 15,16 In addition to setting positive expectations for students at the beginning of the course, at least one study has found a strong correlation between the learning-centeredness of syllabi and the implementation of learning-centered instruction for biology instructors 17 with the strongest correlation between the evidence for learning goals and objectives (on the syllabus) and the learning-centered course design (enacted). With the consideration of the contents of the document, it is reasonable to assume that the syllabus at least gives some insight about how instructors think about course design.…”
Section: Role Of the Course Syllabusmentioning
confidence: 99%
See 2 more Smart Citations
“…9 A learning-focused syllabus can communicate to students that the course is interesting and rigorous and that the instructor cares about and is important to their success. 15,16 In addition to setting positive expectations for students at the beginning of the course, at least one study has found a strong correlation between the learning-centeredness of syllabi and the implementation of learning-centered instruction for biology instructors 17 with the strongest correlation between the evidence for learning goals and objectives (on the syllabus) and the learning-centered course design (enacted). With the consideration of the contents of the document, it is reasonable to assume that the syllabus at least gives some insight about how instructors think about course design.…”
Section: Role Of the Course Syllabusmentioning
confidence: 99%
“…The developers of the Palmer rubric assert that the presence of evidence for learningcenteredness is better evidence of an instructor's actual teaching values than is the absence of evidence for learningcenteredness. Nonetheless, the course syllabus plays an important role in setting expectations for students at the beginning of the semester, 16 and at least one study has found a correlation between syllabus focus and enacted practice. 17 In any case, considering how this document could be more learning-centered in physical chemistry courses may alleviate some of the students' negative perceptions and low expectations for success.…”
Section: ■ Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These syllabi are known as "learner-centered" (Richmond et al, 2019;Weimer, 2002). Such syllabi are characterized by the following items (Wheeler et al, 2019):…”
Section: The Problemmentioning
confidence: 99%
“…Collaborative learning supports students to be clearer about their individual potential in relation to other professions. Studies indicate that syllabi promote students' socialization to their profession; how they are written may narrow students' perspectives and influence their perceptions, and motivation (Wheeler, Palmer, and Aneece 2019). One way to study the socialization into the profession is to study the specific syllabi for each education/ program.…”
Section: Theories Of Socialization In Educationmentioning
confidence: 99%